Study on technical requirements for distributed generators connecting to power grid - Munukutla, Sruti Keerti (2016)
Distributed generation or on-site generation is expected to increase over time with the focus shifting towards energy efficient, sustainable, and reliable means of generating electricity. In order to ensure that the integration of distributed generators does not cause any instability, the power grid companies require that the generator equipment follow certain rules and requirements set by them in the form of "Grid codes". These requirements differ from one country to another due to differences in the topology of the network and hence, study of generator connection requirements cannot be generalized. This thesis deals with the analysis of critical requirements of synchronous generator connection requirements for two grid codes, namely German Grid code & Technical rules defined by Western Power Australia. Among all the requirements, Low voltage ride through capability requires that the connected generator maintain its connection if the voltage at the point of common coupling is above the required Low Voltage Ride Through profile when fault occurs in the power grid. This is one of the most demanding requirements and is hence important to analyse the LVRT characteristics during the modelling phase of a generator system. To study the strong & weak grid conditions, a single machine connected to an infinite bus model was developed. The simulations were performed using MATLAB Simulink. Effects of transmission line lengths, meshed & radial configurations on the transient stability and LVRT capability were assessed for various ratings of generators for grid compliance studies. The observations of the simulations are presented and discussed. The results of the cases studies show that meshed configuration performs better with respect to transient stability.